1997
DOI: 10.1002/actp.1997.010480801
|View full text |Cite
|
Sign up to set email alerts
|

New approaches to advanced polymers by selective cellulose functionalization

Abstract: The uniform structure of cellulose, combined with its hydrophilicity, biocompatibility, chirality, and structure-forming capacity, as well as its broad synthetic potential, make the design of cellulose-based advanced materials a challenge for polysaccharide research. The synthesis of new cellulose products with regiocontrolled pattern of functionalization and of well defined supramolecular nanoscale architectures is a highlight in recent cellulose chemistry. The present feature will discuss regioselective func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 55 publications
0
56
0
Order By: Relevance
“…For example, the tritylation of cellulose has become a well-known and useful method for selective protection of primary hydroxyl groups in this field [7][8][9] . In the course of our studies in the field of polysaccharides 10,11) one of recent research goals is the development of synthesis pathways for a controlled functionalization of the macromolecules both within the AGU and along the polymer chains. In the present paper we wish to report a new attempt to control the functionalization pattern by reacting the secondary hydroxyl groups of 6-O-protected triphenylmethylcellulose products via induced phase separation processes exemplified by the preparation of carboxymethylcellulose (CMC).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the tritylation of cellulose has become a well-known and useful method for selective protection of primary hydroxyl groups in this field [7][8][9] . In the course of our studies in the field of polysaccharides 10,11) one of recent research goals is the development of synthesis pathways for a controlled functionalization of the macromolecules both within the AGU and along the polymer chains. In the present paper we wish to report a new attempt to control the functionalization pattern by reacting the secondary hydroxyl groups of 6-O-protected triphenylmethylcellulose products via induced phase separation processes exemplified by the preparation of carboxymethylcellulose (CMC).…”
Section: Introductionmentioning
confidence: 99%
“…For the design of advanced materials, synthetic modification of cellulose has been conducted to introduce various functionalities. 6 Substitution of some hydroxyl protons causes drastic changes in the physical properties: in fact, silylated cellulose derivatives are often soluble in nonpolar solvents due to the significant reduction in the intermolecular hydrogen bonding. 7,8 For example, Wegner and co-workers 9,10 demonstrated that Langmuir monolayers of trimethylsilylcellulose ͑TMSC͒ could be transferred onto a hydrophobized substrate by the Langmuir-Blodgett ͑LB͒ method.…”
Section: Introductionmentioning
confidence: 99%
“…In other hemocompatibility tests, the sulfate groups in the C-2/3 position of cellulose are much more effective in confering anticlotting activity on the molecule than those in 6 position. [19] However reverse results are reported in regioselectice sulfated chitin derivatives in comparable positions [24] for interpreting the results one has to take into account the validity and comparability of the used tests for antithrombogenicity and athrombogenity for biomaterials and the results of our planed total study. Low level of complement activation is also important for a high standard of hemocompatibility.…”
Section: Discussionmentioning
confidence: 88%
“…Only more recent synthetic reactions have used the regioselective concepts for preparing more defined derivatives. There are exellent reviews for preparing cellulose derivatives and recently for preparing regioselectively sulfated cellulose by Klemm et al [18][19] In contrast to this chitosan derivatives with more defined arranged functional groups in the repeating units were synthesized prior to the cellulose derivatives. The earliest attempt at sulfation of chitosan was that of Karrer et al [20] The product had a DS of 1.7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation